High-pressure CO2-CH4 selective adsorption on covalent organic polymer - Lee, S.-P. (Elsevier B.V., 2018)
Most of the newly discovered gas reservoir has high CO2 content (up to 70), thus pose critical challenges to gas separation process due to the limitation of current acceptable technology. Recent report on COP-1 showed its potential as sorbent for CO2 capture due to its high adsorption capacity, low cost sorbent with good water resistance. However, scarce data on the potential of COP-1 and its selectivity for CO2/CH4 adsorbent for high pressure operation were reported. In this study, the adsorption isotherms were gravimetrically measured using magnetic suspension balance (MSB) within the range of 50â100 bar, at isothermal temperatures of 298, 318, 328 and 338 K. Langmuir and Sips isotherm models were correlated to the adsorption equilibrium data at critical and supercritical conditions. The ideal adsorption selectivities for CO2/CH4 separation were also predicted using Ideal Adsorbed Solution Theory (IAST). The ideal selectivity obtained (â¼22) shows good separation performance for CO2 from CH4 onto COP-1. Furthermore, isosteric heats of adsorption calculated from Clausius-Clapeyron equation reveals that physisorption is the dominant factor for the interaction between adsorbates and surface of COP-1. Results also showed that the isostearic heat of COP-1 is a strong function of temperature and adsorbed amount. Nevertheless, the adsorption behaviour of COP-1 found in this work gives a good indication on the utilization of COP in CO2/CH4 separation for unexploited natural gas reservoir with high CO2 content. Â© 2017 Elsevier B.V.